Evaluation of growth and postharvest ripening of Shinsseiki pears - Lombardi, Sergio Ricardo Bolte; de Moraes, Dario Munt; Camelatto, Darcy (Pesquisa Agropecuaria Brasileira, 2000)
The objective of this work was to determine fruit development and postharvest ripening of Asian pears cv. Shinsseiki (Pyrus pirifolia) treated with different concentrations of 2-chloroethyl phosphonic acid (CEPA). Fruit growth was evaluated at 14 day intervals starting from full bloom; length and diameter of 20 marked fruits were measured in ten plants from an orchard established in Canguçu, RS, Brazil. At maximum growth, 168 fruits were harvested and submitted to immersion for five minutes in solutions of zero, 50, 100 and 150 mg L-1 of CEPA. After the treatment, pears were held at room temperature, for 18 days. Seven evaluations took place, at three-day intervals. 'Shinsseiki' pears show growth curve of the simple sigmoidal type, evolution in the weight gain and total soluble solids (TSS), reduction in total titrable acidity (TTA) and flesh firmness with the complete growth. After postharvest treatments, fast evolution of the superficial color was observed, with increasing CEPA concentrations. A significant weight loss and reduction in the flesh firmness were observed. Small increases in the values of TTA and TSS and a constant ratio TSS/TTA were found. Pears of the cultivar Shinsseiki have a climacteric behavior and a 50 mg L-1 CEPA solution is enough to anticipate ripening in 9 to 12 days.
Keywords: Pyrus pirifolia; postharvest physiology; ethylene